Distance Learning In The Covid-19 Pandemic Based On Information And Communication Technology To Strengthen Country - Khaerudin (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2022)
The purpose of this research is to find out about distance learning during the Covid-19 pandemic and to provide the right learning model. The research method used is a library model obtained from documents and learning articles, with pandemic online learning. Data were analyzed with descriptive qualitative, to reveal the phenomena and events that occurred. Valid data source analysis. The results of the research can explain the problems in online learning, and the components of online learning, as well as meaningful collective learning in online learning, namely: (1). Pedagogic constructs, (2). Learning strategies, (3). Pedagogic tools or Internet and web-based technologies. Analyze and provide input on influencing facts, namely: (1). Internet speed. (2). There is no social interaction, between lecturers with students, (3). Lecturers are less able to control students. Online learning is an alternative solution to organizing education through learning during the Covid-19 pandemic, so by utilizing information and communication technology it can carry out systematic learning, achieve educational goals, and improve the quality of graduates.